Inovasi Program Sakera Mesem dalam Meningkatkan Kualitas Pelayanan Publik - Nadiatussilmi, Nadiatussilmi; Hayat, Hayat; Anadza, Hirshi (CV. Publikasi Indonesia, 2022)
This research is a significant research in selecting the idea of ​​implementing policies related to the improvement of a Sakera Mesem program and the constraint factors that led to the idea of ​​regulating the quality of population document services at the Population and Civil Registration Office of Sampang Regency. The purpose of this research is to describe and analyze the innovations of the Sakera Mesem program in improving the quality of public services at the Department of Population and Civil Registration of Sampang Regency. In this study used qualitative research methods, qualitative research methods are research that analyzes something that appears in the field, data collection techniques used are interviews and observations and documentation. From the results of the discussion, it can be obtained the results of research that analyzes the development of the